History of islamic education and the digital identity of minangkabau adolescents: an anthropological study of social media - Sandora, Lisna; Yulniza, Yulniza (Jurnal Konseling dan Pendidikan, 2025)
This qualitative literature review explores the intersection of the history of Islamic education and the digital identity of Minangkabau adolescents, with a particular focus on their use of social media. Islamic education has long been a cornerstone of cultural and social identity in Minangkabau society, deeply influencing the moral, religious, and social values of its people. Over time, the integration of modern technological platforms, particularly social media, has significantly transformed how Minangkabau adolescents engage with their cultural heritage and religious education. This study applies an anthropological lens to understand how these adolescents navigate their digital identities, balancing traditional Islamic values with contemporary digital influences. By reviewing existing literature on Islamic education, digital culture, and identity formation, this research highlights the challenges and opportunities faced by young Minangkabau in maintaining cultural authenticity while participating in globalized online spaces. The findings underscore the dual role of social media as both a platform for cultural expression and a space for generational tension, where traditional values often clash with modern, global digital trends. This study aims to contribute to a deeper understanding of the evolving relationship between cultural heritage, religious education, and the digital world for indigenous adolescents, offering insights into the broader impacts of digitalization on youth identity formation in post-colonial, Muslim-majority societies.